Innovative Technologies in Vocal Training: Technological Culture Formation of Future Musical Art Teachers - Ovcharenko, Nataliya; Samoilenko, Oleksandra; Moskva, Olena; Chebotarenko, Olha (Journal of History Culture and Art Research, 2020)
Under the conditions of present-day modernization of education, the urgency of dealing with educational issues and challenges in terms of the coronavirus pandemic, the teacher’s technological culture enhancement who is capable to effectively apply innovative technologies in the educational process has acquired particular significance. Therefore, special attention is paid today to the formation of future music teachers’ technological culture by means of applying innovative technologies in vocal training at the institution of higher artistic and artistic-pedagogical education. The technological culture of the teacher is considered as a professional and personal phenomenon based on value-and-technology worldview and way of thinking, skills in the application of technological knowledge, those formed and implemented in creative artistic and pedagogical activities as well as the ability to creatively use pedagogical tools. Students have to master a wide range of technologies for teaching singing and then use them in their practical activities as music teachers, namely: technologies aimed at mastering performing and methodological foundations of singing for future teachers; information and computer technologies, including remote ones, aimed at teaching the art of singing in remote access and mastering the basics of sound amplification equipment by both future performers and music teachers; technologies that have a music therapy and healthcare effect. The methodological basis for technological culture formation of future music teachers in the process of vocal training features such scientific approaches as: culturological, technological, competence approach along with creative one. In order to effectively form the technological culture of future musical art teachers, the following elements have been determined: the structure of this phenomenon, which includes axiological-culturological, epistemological-emotional, technological and activity approaches as well as creative-professional one; their level of formation is determined by the identified criteria, in particular: value-axiological, cognitive-emotional, vocal-operational and creative-professional.